To find the average rate of change of the function \( f(x) = x^2 + 6x + 8 \) over the interval \([-2, 0]\), we will use the formula for average rate of change:
\[ \text{Average Rate of Change} = \frac{f(b) - f(a)}{b - a} \]
where \( a = -2 \) and \( b = 0 \).
First, we need to calculate \( f(-2) \) and \( f(0) \):
-
Calculate \( f(-2) \): \[ f(-2) = (-2)^2 + 6(-2) + 8 = 4 - 12 + 8 = 0 \]
-
Calculate \( f(0) \): \[ f(0) = (0)^2 + 6(0) + 8 = 0 + 0 + 8 = 8 \]
Now that we have both function values, we can plug these into the average rate of change formula:
\[ \text{Average Rate of Change} = \frac{f(0) - f(-2)}{0 - (-2)} = \frac{8 - 0}{0 + 2} = \frac{8}{2} = 4 \]
Thus, the average rate of change over the interval \([-2, 0]\) is \(\boxed{4}\).